PEMAHAMAN GURU IPA DALAM STRATEGI PEMBELAJARAN PETA PIKIRAN (MIND MAP) - Keliat, Natalia Rosa (Prodi Teknologi Pendidikan, 2017)
Abstract. This researchs were conducted in Salatiga primary high school, Central Java and the subject of were taken from 23 science teachers which used interview and observation tech-niques. The aim of this study was firstly, to assess learning strategies of science in Salatiga prima-ry high school, and secondly to assess the obstacles and constraints that faced the science teach-ers in the implementation of learning strategies in the classroom. Further more the percentage of the understanding and application of mind map model, and also to assess the obstacles and con-straints in the implementation of mind map in the classroom. Data were analyzed by using de-scriptive qualitative method. The results showed that the percentage of science teachers using discussion methods are 78.26%, 21.74% by concept maps, 30.43% by demonstrations, 39.13% by lectures, 34.78% using mind map respectively by other strategies such as card games, quiz, pro-ject based learning, discovery, problem based learning, contextual teaching learning, and inquiry is 43,8%. Teachers faced difficulty to allocate the time in the classroom because students who had lower levels of cognitive abilities require a longer time to understand the strategies in the class-room. The percentage of teachers using mind map in teaching only reach at 34.78%, while 65.22% teachers still not applying yet. Results of interview which were conducted approximately 47.83% to the teachers who understand the learning mechanisms model of mind map, and 52.17% did not understand the principles of learning using mind map. However, in its application in the classroom teachers face some problems, for example, it is take time to implemented, and the other subjects difficult to finished on time. More over, other constraints that faced are the students still have difficulty in making mind map because lack of exercise, as well as students who are already familiar with the habit pattern of teacher using teaching center.Abstrak. Penelitian ini dilaksanakan di SMP Salatiga, Jawa Tengah dengan subjek penelitan adalah guru bidang studi IPA yang berjumlah 23 orang dengan menggunakan teknik wawancara dan observasi. Penelitian ini bertujuan untuk mendata strategi pembelajaran IPA yang dilakukan guru SMP Kota Salatiga, kendala yang dihadapi guru dalam melaksanakan strategi pembelajaran di kelas, persentase pemahaman dan penerapan mind map oleh guru IPA SMP Kota Salatiga, serta kendala dalam melaksanakan strategi mind map di kelas. Analisis penelitian yang digunakan adalah deskriptif kualitatif. Hasil menunjukkan persentase guru IPA yang menggunakan strategi diskusi mencapai 78.26%, peta konsep 21,74%, demonstrasi 30,43%, ce-ramah 39,13%, mind map 34,78% dan strategi-strategi lain seperti permainan kartu, cerdas cer-mat, project based learning, discovery, problem based learning, CTL, inquiry mencapai 43,8%. Dalam menerapkan strategi yang bervariasi guru mengalami kesulitan dalam mengatur alokasi waktu pembelajaran di kelas dikarenakan peserta didik yang memiliki tingkat kemampuan kogni-tif rendah membutuhkan waktu yang lebih lama untuk memahami strategi pembelajaran yang dipakai di kelas. Dalam penerapan mind map, menunjukkan persentase jumlah guru yang menggunakan mind map dalam pembelajaran di SMP Kota Salatiga hanya mencapai 34,78% dan yang masih belum menerapkan pembelajaran model mind map mencapai 65,22%. Berdasarkan hasil wawancara diketahui bahwa sekitar 47,83% guru tersebut memahami prosedur pembelajaranmodel mind map, selebihnya sebesar 52,17% mengatakan belum memahami prinsip pembelajaran menggunakan mind map. Guru menjelaskan bahwa mind map sangat potensial digunakan se-bagai suatu teknik untuk meningkatkan pembelajaran peserta didik. Meskipun demikian, dalam penerapannya di kelas guru mengalami kendala dalam pengaplikasian mind map, misalnya dibu-tuhkan waktu yang cukup lama untuk menerapkan mind map sehingga materi lainnya tidak dapat diselesaikan tepat waktu. Selain itu, kendala lain seperti siswa masih kesulitan dalam membuat mind map dikarenakan kurang latihan, serta siswa yang sudah terbiasa dengan kebiasaan pola pengajaran teacher center sehingga model mind map ini dianggap sulit bagi siswa.Â